(3QSGdI aj eYQaI ESJNQGL CYeGd Gddjd hGdfgGQs - (3jMji Hf eMeO Hf eMeO Hf YHO GdQMef GdMWGH, GdQYjfqj GdCUd, Gdecqj GdeGdcj,J (B995 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg ebOeI eNJUQI ai eYQaI GSJNQGL CYeGd Gddjd hGdfgGQ ef QHY GdaGFOg GdeSeGg HGdQHY GdeLjH s
(3BNQgG (B:s
(3Ke Jfbd GdNjW Edi LjH GdJeGe aEf bWY GdeQi efg eKd Pdc GdYOO agh UMjM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B169 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B226s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B393 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B217) s
Keywords: (3Gdadcs